2018
DOI: 10.1177/1526602818797986
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Reversal of Blood Flow During Transcarotid Artery Revascularization Does Not Change Brain Electrical Activity in Lead-In Cases of the ROADSTER 1 Multicenter Trial

Abstract: Temporary reversal of blood flow during TCAR is a safe maneuver and does not cause cerebral ischemia in the vast majority of patients, including those with contralateral carotid occlusion. Carotid stenting performed with reversed blood flow mitigates cerebral embolization and periprocedural stroke without concern for brain ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…A meta-analysis showed that the perioperative stroke and death rates of TCAR may be comparable to those with CEA, while TCAR may outperform CEA in terms of cranial nerve injuries. 24 In TCAR, not only is the common carotid artery clamped, but flow reversal is also used to provide cerebral 25 Similarly, our study showed no statistically significant difference in the risk of stroke or death between TCAR and CEA in patients with CCO. We hypothesize that the flow reversal may improve cerebral perfusion through collaterals from the posterior circulation, even in patients with CCO.…”
Section: Discussionmentioning
confidence: 54%
“…A meta-analysis showed that the perioperative stroke and death rates of TCAR may be comparable to those with CEA, while TCAR may outperform CEA in terms of cranial nerve injuries. 24 In TCAR, not only is the common carotid artery clamped, but flow reversal is also used to provide cerebral 25 Similarly, our study showed no statistically significant difference in the risk of stroke or death between TCAR and CEA in patients with CCO. We hypothesize that the flow reversal may improve cerebral perfusion through collaterals from the posterior circulation, even in patients with CCO.…”
Section: Discussionmentioning
confidence: 54%
“…Clamp-induced EEG changes usually occur within the first 4 to 5 minutes after cross-clamping and increase risk of long-term stroke up to six times 21, 22, 23. In the Safety and Efficacy Study for Reverse Flow Used During Carotid Artery Stenting Procedure (ROADSTER), the mean flow reversal time for TCAR was 12.9 minutes 11 , 24 . Flow reversal leads to concern about cerebral perfusion for patients who do not have adequate circulation through the circle of Willis.…”
Section: Discussionmentioning
confidence: 99%
“…During TCAR, the relatively longer time of flow reversal without a mechanism to reliably provide antegrade flow to the affected cerebral hemisphere does support the utility of regular use of EEG during TCAR. A post hoc analysis of the ROADSTER trial found that only 1.2% of patients exhibited slight EEG changes during flow reversal that resolved with blood pressure elevation, with the authors concluding that TCAR can be performed without the use of EEG 24 . Since 2017, our institution has performed 85 TCAR procedures with a stroke rate of 1.2% and overall stroke and death rate of 1.2%.…”
Section: Discussionmentioning
confidence: 99%
“…With recent studies suggesting promising 30-day stroke and mortality rates following TCAR 5 8 , we chose to utilize this less invasive approach for the treatment of internal carotid stenosis treatment. We also preferred an ascending aorta to proximal CCA bypass as it provides durability and historically strong 5 and 10 year patency rates at 94% and 88%, respectively.…”
Section: Discussionmentioning
confidence: 99%